1989
DOI: 10.1001/archotol.1989.01860250039022
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Interferon Levels in Patients With Bell's Palsy

Abstract: \s=b\Serum interferon (IFN) levels were analyzed in patients with Bell's palsy to study the immune response in the disease. Serum samples from 91 patients were assayed for antiviral activity using a bioassay. The IFN levels in the serum were elevated in the acute and convalescent phases as compared with control subjects. The serum IFN-\g=g\levels were analyzed by radioimmunoassay in 32 of the patients: the IFN-\g=g\levels were alike in the acute and convalescent phases and the control subjects. Neutralization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…An infectious cause associated with an autoimmune response may be in volved in the disease [1,2], This is in agree ment with the finding of a prolonged immu nological response during the course of the disease [3]. In accordance with an immuno logical dysfunction, elevated serum levels of complement component Clq-and comple ment component C3-containing circulating immune complexes have been reported in the acute stage of Bell's palsy [4,5].…”
Section: Introductionsupporting
confidence: 67%
“…An infectious cause associated with an autoimmune response may be in volved in the disease [1,2], This is in agree ment with the finding of a prolonged immu nological response during the course of the disease [3]. In accordance with an immuno logical dysfunction, elevated serum levels of complement component Clq-and comple ment component C3-containing circulating immune complexes have been reported in the acute stage of Bell's palsy [4,5].…”
Section: Introductionsupporting
confidence: 67%
“…The circulating IFN-~ is unusual in that it shows an acid lability not typically seen for IFN-~t. Acid labile serum IFN-~ is also seen in a number of different clinical scenarios, including patients with lupus Yee et al, 1989), multiple sclerosis (unpublished results), juvenile arthritis (Arvin and Miller, 1984), Bell's palsy (Jonsson et al, 1989) and some acute viral infections. This serum IFN does not appear to reflect expression of a unique IFN-~ gene or genes whose product is intrinsically acid labile, but rather appears to be conferred by other as yet unidentified serum components (Yee et al, 1989).…”
Section: Ifn Production In Aidsmentioning
confidence: 92%
“…A recent report by Austin et al 3 demonstrated the clinical usefulness of prednisone when compared with placebo in patients with Bell's palsy. However, in the current literature the viral pathogenetic hypothesis is gaining acceptance, suggesting that the herpes simplex virus may play a fundamental role in IFNP 4‐8 . Viral DNA has been recently identified in endoneural fluid and muscle of patients with IFNP, suggesting that herpes simplex virus plays an important role in the etiopathogenesis of IFNP 9,10 .…”
Section: Introductionmentioning
confidence: 99%